2007
DOI: 10.1093/sleep/30.6.737
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship of Subjective Sleep Quality, Pain, and Quality of Life in Advanced Cancer Patients

Abstract: Quality of sleep in patients suffering from stage IV cancer was significantly decreased. Demographic data and clinical variables of cancers did not affect the PSQI Global Sleep Quality score. The use of the mediation model also provides evidence that quality of sleep, quality of life, pain, and opioids are strictly correlated each other.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
53
4
12

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(84 citation statements)
references
References 22 publications
15
53
4
12
Order By: Relevance
“…This finding emphasizes the relationship between the already known sleep disorders and quality of life studied by several national and international authors (ROSCOE et al, 2007;MYSTAKIDOU et al, 2007).…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…This finding emphasizes the relationship between the already known sleep disorders and quality of life studied by several national and international authors (ROSCOE et al, 2007;MYSTAKIDOU et al, 2007).…”
Section: Discussionsupporting
confidence: 73%
“…Other studies obtained similar results: 7.7 in elderly patients with cancer under outpatient chemotherapy and 12.00 in patients with advanced cancer (MYSTAKIDOU et al, 2007;SCHLOSSER, 2011). In another study, 73.9% had an overall score higher than five (BARICHELLO et al, 2009).…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…Their findings are consistent with those in the present study. Pain, which is one of the main factors affecting depression and sleep disturbance in cancer patients 50,52 , might partly explain the relationships of cipn with psychological distress and sleep disturbance. Chemotherapy-induced peripheral neuropathy can cause neuropathic pain 49 , and patients with pain in their hands or feet are at higher risk for developing depression, anxiety, and sleep disturbances.…”
Section: Discussionmentioning
confidence: 99%
“…32 Another study in 2007 found a dose-dependent effect of CPAP on improvement of quality of life. 33 Other studies also showed that a daily average of 3 h of CPAP use is sufficient to decrease DBP in subjects with severe OSA and hypertension. 29,30 However, one report showed that CPAP therapy has little effect on reducing blood pressure in subjects with OSA.…”
Section: Blood Pressure and Cpapmentioning
confidence: 97%